ANALISIS KINERJA KEUANGAN PADA PT. PEGADAIAN (PERSERO) PERIODE 2014-2018 - Arista, Puput Madya; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The development of financial position has a very important meaning for the company. To see whether a company is healthy or not can only discuss the circumstances just physical. The most important factor to be able to see the development of a company lies in its finances. One tool used to find out corporate finance statement. And PT. Pegadaian (Persero) also needs to be recognized finance to find out the company financial’s performance so far. Methods commonly used in assessing the performance achieved in a company that is financial ratio analysis. Financial ratios are the figures obtained from the comparison of the financial reporting post with another post. Financial ratios used to analyze financial performance are liquidity, profitability and activity. The results of this analysis are company performance when measured as a whole shows the financial performance included in the fairly healthy category. Financial performance of liquidity ratios when measured using current ratio analysis shows unhealthy results, when measured by cash ratios showing unhealthy results. Solvency financial performance when measured using the ratio of own capital to total assets shows a healthy performance. The financial performance of profitability when measured using the ROI ratio shows a fairly healthy performance, when measured using the ROE ratio shows a healthy performance. The financial performance of activities when measured using the inventory turnover ratio shows a very healthy performance, when measured using the total assets turnover ratio it shows an unhealthy performance. Keywords: Financial Performance, Financial Ratio, liquidity, solvency, profitability, activity.